Public transport network improvements as a catalyst for integrated land use-transport development: lessons from case studies of Copenhagen, Curitiba, Hong Kong and Seoul - Mntungwa, Phila Rachel (Department of Civil Engineering, 2025)
Background: Challenges in the provision of public transport services in South Africa prompted the government to transform the public transport system during the mid-2000s. This led to the development of the Public Transport Strategy and Public Transport Action Plan in 2007. This resulted in the implementation of Bus Rapid Transit (BRT) systems in various cities, such as Johannesburg, Cape Town and Tshwane. Another notable public transport project was the implementation of the Gautrain rapid rail transit project. The BRT systems in South Africa have faced many implementation and operations challenges. These challenges include low ridership and difficulties in covering operating costs. The intentions of an integrated public transport system have, therefore, not been fully realised. Aim This study aims to identify characteristics of four case cities before and after the implementation of their BRT or rail transit systems, focusing on land value capture, transit-oriented development, land use patterns, and travel behaviour. This includes presenting information related to planning and institutional arrangements, financial and operational arrangements of the systems. It is hoped that lessons can be learnt from these case study cities and be applied to the South African context. Method Cumulative multiple case studies were conducted in the cities that had implemented BRT (Curitiba and Seoul) and the cities that had implemented transit rail systems (Copenhagen and Hong Kong). Qualitative information was collected from online documents, including journal articles, academic research reports, information from organisational websites, internet information, and online newspaper articles. Based on the information collected, a synthesis matrix was then created, which captured the similarities and differences of the case studies under different themes and thereafter identified lessons learnt. Findings One main similarity in these case studies was political involvement before the implementation of the projects, while one of the main differences was the different funding mechanisms used to implement these projects. The four case studies showed that successful implementation of their projects entailed a large-scale implementation of the public transport network improvement project. In other words, a citywide public transport network serves as a catalyst for integrated land use-transport development. Conclusion This research study concludes that political involvement, stakeholder engagement, funding framework, and implementation of a catalytic project for integrated land use transport development at a large scale are crucial for successful implementation of different phases of BRT or rail transit projects.